Auditory agnosia for environmental sounds in Alzheimer’s disease: Effects on daily life - J.A. Coebergh; S. McDowell; T.C.A.M. van Woerkom; J.P. Koopman; J.L. Mulder; F.R.E. Smink; J.D. Blom; S.F.T.M. de Bruijn (IBRO Neuroscience Reports)
Background: Auditory agnosia for environmental sounds is a type of agnosia attributed to central auditory dysfunction. It is common in Alzheimer’s disease, and is associated with peripheral hearing loss, although independent of it, and presumed independent of language deficits. The effects of this type of agnosia on daily life in Alzheimer’s disease are unknown. Objective: We aimed to assess the impact of auditory agnosia for environmental sounds in people with Alzheimer’s disease while also exploring the role of unrecognized hearing loss. Methods: We tested 34 home-dwelling people with Alzheimer’s disease and a mean MMSE of 21.9 with the aid of a sound naming and recognition test, the tailor-made EESAA (Experiencing Environmental Sounds in Auditory Agnosia) questionnaire, the ADQRL (Alzheimer’s Disease-Related Quality of Life) scale, and speech and tone audiometry. Results: Some 57 % of our 34 participants showed clinical signs of auditory agnosia for environmental sounds, and 47 % had undetected hearing loss to such an extent that it made them eligible for a hearing aid. Although the two factors appear to be independent, their joint effect can impact people’s daily functioning. Nonetheless, we found them to have only little impact on the participants’ quality of life as measured by the ADQRL, possibly because most of them lived in a sheltered environment, and some moreover showed anosognosia for their agnosia. Conclusion: Difficulties recognizing environmental sounds in daily life are very common in people with Alzheimer’s disease. Although we found no direct relation with quality of life as measured by a questionnaire, awareness of auditory agnosia for environmental sounds is still important since it may help explain why function declines. The additional finding that 47 % of people in this group had unrecognized hearing loss shows that self-assessment of hearing is often inaccurate in Alzheimer’s disease, with implications for daily practice where clinicians might only explore hearing loss when acknowledged by their patient. On the basis of our findings we advise further longitudinal, multi-year studies of hearing screening and rehabilitation in Alzheimer’s disease, if possible starting during its prodromal stage, something supported by findings in a large trials suggesting that hearing interventions might be slowing cognitive decline in an older population at risk of this.